Optimization of Design of Drilled Shaft Foundations by Lateral Load Testing (94ee84ca-5eda-40d1-bba2-d7742a925002) - Donald R. Clark (Deep Foundations Institute, 2017)
"Drilled shafts are being used as foundation support for parabolic solar troughs at the Genesis Solar Project being constructed near Blythe, California. Three types of drilled shaft foundations are required for the project. At project build-out, there will be a total of 23,008 drilled shafts installed at the site. Preliminary designs for the axial and lateral capacity of the drilled piers were based on conventional geotechnical engineering methodologies and soil-structure interaction. The drilled shafts and subsurface conditions were modeled through the use of the computer program LPILE v6.0.Conducting lateral load testing of drilled shafts was considered appropriate to confirm or modify the geotechnical parameters used in the preliminary design. The lateral load testing program was conducted to provide site-specific test data that would allow the design engineers (both geotechnical and structural) to predict the actual performance and adequacy of the proposed drilled shaft foundations and improve the efficiency and hopefully reduce project costs.The lateral load testing was conducted within two solar fields at the site. Three pairs of drilled shaft foundations were installed in each field, instrumented, and laterally loaded to determine load-deflection response. A value-engineered option, proposed by one of the drilled shaft contractors, was also load tested. The results of the load-deflection data obtained in the field was used to modify the soil modeling used in the original L-PILE analyses and adjust the production drilled shaft lengths.Based on the results of the lateral load testing, the in-situ moduli of the subsurface soils were significantly increased over that assumed in the preliminary analyses. Based on the final soil-structure interaction analyses, the preliminary drilled shaft lengths were reduced by 2 to 2-1/2 feet. This resulted in an overall reduction of 55,654 feet of drilled shaft construction on the entire project, a savings of approximately 16.5% over the preliminary"